Association with Amino Acids Does Not Enhance Efficacy of Polymerized Liposomes As a System for Lung Gene Delivery - Bandeira, Elga; Lopes-Pacheco, Miquéias; Chiaramoni, Nadia; Ferreira, Débora; Fernandez-Ruocco, Maria J.; Prieto, Maria J.; Maron-Gutierrez, Tatiana; Perrotta, Ramiro M.; de Castro-Faria-Neto, Hugo C.; Rocco, Patricia R. M.; Alonso, Silvia del Valle; Morales, Marcelo M. (Frontiers in Physiology, 2016)
Development of improved drug and gene delivery systems directly into the lungs is highly desirable given the important burden of respiratory diseases. We aimed to evaluate the safety and efficacy of liposomes composed of photopolymerized lipids (1,2-bis-(tricosa-10,12-diynoyl)-sn-glycero-3-phosphocholine) associated with amino acids as vectors for gene delivery into the lungs of healthy animals. Lipopolymer vesicles, in particular, are more stable than other types of liposomes. In this study, lipopolymers were associated with L-arginine, L-tryptophan, or L-cysteine. We hypothesized that the addition of these amino acids would enhance the efficacy of gene delivery to the lungs by the lipopolymers. L-Arginine showed the highest association efficiency due to its positive charge and better surface interactions. None of the formulations caused inflammation or altered lung mechanics, suggesting that these lipopolymers can be safely administered as aerosols. All formulations were able to induce eGFP mRNA expression in lung tissue, but the addition of amino acids reduced delivery efficacy when compared with the simple lipopolymer particle. These results indicate that this system could be further explored for gene or drug delivery targeting lung diseases.